2004
DOI: 10.2135/cropsci2004.1132
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species Diversity and Management of Temperate Forage and Grazing Land Ecosystems

Abstract: More than a century since Charles Darwin stated that diverse grasslands produce more herbage than monocultures, scientists still debate the relationship between species diversity and ecosystem function. Postulated benefits of diversity in experimental grasslands include greater and more stable primary production along with more efficient nutrient use. These benefits have been extrapolated to forage and grazing land systems with little supporting objective data. Most information on the potential benefits of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
178
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(190 citation statements)
references
References 100 publications
6
178
1
5
Order By: Relevance
“…For instance, higher diversity has been found to reduce the vulnerability of grassland to climatic extreme events such as droughts as well as to pests and diseases (e.g. Kahmen et al, 2005, Lin 2011, Sanderson et al, 2004, Vogel et al, 2012. The higher temporal stability of production resulting from higher species diversity might be additionally valued by farmers because a less volatile biomass production increases the utility of a risk-averse decision maker.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, higher diversity has been found to reduce the vulnerability of grassland to climatic extreme events such as droughts as well as to pests and diseases (e.g. Kahmen et al, 2005, Lin 2011, Sanderson et al, 2004, Vogel et al, 2012. The higher temporal stability of production resulting from higher species diversity might be additionally valued by farmers because a less volatile biomass production increases the utility of a risk-averse decision maker.…”
Section: Introductionmentioning
confidence: 99%
“…These services include ecosystem processes with direct functional benefits in an agricultural context such as yield, decomposition, nutrient leaching, pollination, soil conservation and resistance to weed invasion along with forage stability under changing climatic conditions. Other goals comprise ecologically important services such as enhanced carbon sequestration and the mitigation of greenhouse gas emissions as well as non-market benefits such as land conservation, the maintenance of landscape structure or even aesthetic values (Sanderson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…If these results were also valid under nutrient-rich conditions, management for increased species diversity would be an ecological approach to enhancing the multifunctionality of grasslands (Sanderson et al, 2004;Hector and Loreau, 2005;Hooper et al, 2005) and could even provide additional benefits for biodiversity conservation (Robertson and Swinton, 2005;Tscharntke et al, 2005). Strong evidence for this approach comes from the European-wide COST experiment which recently showed that even a moderate increase of plant species richness from 1 to 4 species had strong positive effects in intensively managed grasslands (Kirwan et al, 2007).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of weeds was higher in low level of soil gleying, at a high part of the slope. It is considered that the poorer soils create conditions for increase in the species diversity [SANDERSON et al, 2004] . The contradiction with the results of the mentioned author could be due to difference in the geographical conditions [PEETERS and JENSSENS, 1998 ] or to the peculiarities of the species composition of the discussed plant communities.…”
mentioning
confidence: 99%